2016
DOI: 10.1007/s12665-016-5789-9
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year change of total phosphorous pollution in the Min River, an upstream tributary of the Three Gorges Reservoir

Abstract: Understanding the spatial and temporal variation of nutrient concentrations, loads and their distribution from upstream tributaries is important for management of large lakes and reservoirs. The Min River is an important tributary of the upper reaches of the Three Gorges Reservoir (TGR) that contributes about 20 % of the inflow water from the Yangtze River to the TGR. It is also one of the main phosphorous sources of the TGR. In this study, total phosphorous (TP) concentrations and hydrological data from 2004 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…The study was conducted at a revegetation demonstration site of the Ruxi watershed of Zhong County, Chongqing Municipality (N30°24′16′′ and E108°08′03′′), near the riparian zone of the TGR. After the TGR reached an average water storage level of 175 m in 2010, a very large area of land–water ecotone formed, covering an area of nearly 350 km 2 ( Yangtze River Water Resources Commission, 1999 ; Wang, 2003 ; Li et al, 2013 ; Ren et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted at a revegetation demonstration site of the Ruxi watershed of Zhong County, Chongqing Municipality (N30°24′16′′ and E108°08′03′′), near the riparian zone of the TGR. After the TGR reached an average water storage level of 175 m in 2010, a very large area of land–water ecotone formed, covering an area of nearly 350 km 2 ( Yangtze River Water Resources Commission, 1999 ; Wang, 2003 ; Li et al, 2013 ; Ren et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Similar factors have been recognized in the Min River. For example, temperature and precipitation were increased by around 1.5 • C and 390 mm on average in 2015 compared with 1979 in the basin, respectively; human interferences, such as land-use/cover changes under urbanization, dam construction, and agriculture, have been intensified during the past decades (Ma et al, 2020;Ren et al, 2016;Zhao et al, 2016); several invasive species have been identified in the basin (Deng et al, 2020). The synergic effect of these factors might contribute to the loss of habitat suitability for fishes in the Min River.…”
Section: Importance Of Environmental Factors Driving Functional Diversitymentioning
confidence: 99%
“…Several invasive species have been identified in this river (Deng et al, 2020). Human interferences, such as urbanization, dam construction, and agriculture, have inevitably changed its ecological environments (Ma et al, 2020;Ren et al, 2016;Zhao et al, 2016). Temperature and precipitation are continuously changing in the basin (Deng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the decreasing water quality has become a major environmental concern in the TGR 5,6 . Studies have shown that algal blooms frequently develop in the tributary backwaters of the TGR due to the accumulation of nutrients [e.g., nitrogen (N) and phosphorus (P)] triggered by these water level changes in the riparian zone 7,8 . Riparian vegetation restoration is a crucial step for addressing the abovementioned environmental issues of the TGR 9,10 .…”
mentioning
confidence: 99%